Essays on business cycles and stock markets in the OIC - Arshad, Shaista (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2016)
Over the past decades, much research has gone into establishing a link between business cycles and stock market as stock prices correlate with future economic activity on the basis that economic growth forms the source of corporate profits paid out to stockholders. It becomes imperative to assess empirically the stock market's efficiency, volatility and integration with other markets to determine whether it is able to withstand influxes of capital. This thesis focuses on the OIC where despite high developmental potential, OIC stock exchanges are characterized with low levels of liquidity. Understanding where the OIC member states stand with these aspects will allow for formulating policies for better wealth management and efficient investments, which in turn promotes economic development. The first essay looks into the relationship between business cycles and stock market volatility using a multi-sequential analysis. It is found that in most parts our results support the classical belief that stock market volatility is lower in good times than in bad times. The second essay endeavours to test the weak-form Efficient Market Hypothesis for OIC member states. The results indicate an overall trend of improving efficiency throughout the sample period. The final essay focuses on market integration of OIC member countries; the results show that within the OIC, only a few countries, namely Malaysia, Indonesia and Turkey display higher levels of integration with relatively small variations over time. The other countries are confined to lower levels of market integration. In light of the ineffectiveness of the OIC stock markets, the thesis introduces the use of Islamic stock markets as alternative to conventional stock markets to enhance the economic performance of member countries and the region as a whole. Furthermore, as Muslim countries, OIC member countries must strive to strengthen the Islamic fundamentals.